2010
DOI: 10.1542/peds.2010-0507
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors in Children Hospitalized With RSV Bronchiolitis Versus Non–RSV Bronchiolitis

Abstract: BACKGROUND The trends in hospitalization rates and risk factors for severe bronchiolitis have not been recently described, especially after the routine implementation of prophylaxis for respiratory syncytial virus (RSV) infections. OBJECTIVES To define the burden of hospitalizations related to RSV and non-RSV bronchiolitis in a tertiary-care children’s hospital from 2002 to 2007 and to identify the risk factors associated with severe disease. METHODS Medical records of patients hospitalized for bronchiolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
224
7
22

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(285 citation statements)
references
References 21 publications
26
224
7
22
Order By: Relevance
“…Tablo II: Viral ASYE nedeniyle yatırılan hastaların demografik özellikleri. RSV ilişkili enfeksiyonların daha ağır klinik seyire neden olduğu bildirilmektedir (4,9,12,13). Viral etken olarak RSV saptanan yenidoğanların, RSV dışı virüs saptananlara göre daha ağır solunum sıkıntısı bulgularının olduğu, oksijen gereksinimi nedeniyle hastaneye yatış oranlarının daha fazla olduğu bildirilmiştir (14).…”
Section: Introductionunclassified
“…Tablo II: Viral ASYE nedeniyle yatırılan hastaların demografik özellikleri. RSV ilişkili enfeksiyonların daha ağır klinik seyire neden olduğu bildirilmektedir (4,9,12,13). Viral etken olarak RSV saptanan yenidoğanların, RSV dışı virüs saptananlara göre daha ağır solunum sıkıntısı bulgularının olduğu, oksijen gereksinimi nedeniyle hastaneye yatış oranlarının daha fazla olduğu bildirilmiştir (14).…”
Section: Introductionunclassified
“…Acute bronchiolitis is the main cause of respiratory illness requiring hospitalization in children under 2 years of age and the trend in hospitalization rate has been increasing in recent years (1). Mainly due to Respiratory Syncytial Virus (RSV) infection, the disease leads to hospitalization in only I% of the children.…”
mentioning
confidence: 99%
“…For children with bronchiolitis, García et al [57][58][59] found three predictors of ICU admission: virus species (RSV vs. non-RSV), atelectasis/condensation, and co-infection. For children with RSV infection, Verger et al [60][61][62][63][64][65][66][67][68] identified several risk factors for ICU admission: immature lung development, prematurity, chronic lung disease, congenital heart disease (defined as congestive heart failure, cyanosis, or pulmonary hypertension), neuromuscular impairment, high nasal RSV viral load, surfactant protein A2 polymorphism, age < 6 weeks, neurological disease, cerebral palsy, male gender, lung consolidation, lethargy, grunting, high arterial PaCO 2 , an ED visit in the past week, presence of moderate to severe retractions, inadequate oral intake upon presentation in the ED, and mental retardation.…”
Section: Predicting Icu Admissionmentioning
confidence: 99%
“…For patients hospitalized with bronchiolitis, García et al [57,86,87] identified several predictors of using supplemental oxygen: household tobacco smoking, cyanosis, sternal retraction, intercostal recession, chronic lung disease, trisomy 21, congenital heart disease, virus species, and prematurity. For bronchiolitis patients in the ED and inpatient ward, McCallum et al [88] used a bronchiolitis severity score to predict the use of supplemental oxygen at 12 and 24 hours, with a low AUC of 68% and 75%, respectively.…”
Section: Predicting the Use Of Supplemental Oxygenmentioning
confidence: 99%